FORMULATION AND EVALUATION OF FLOATING DRUG DELIVERY SYSTEM OF REPAGLINIDE - Begum, Asma; RANI, G UMA (Asian Journal of Pharmaceutical and Clinical Research, 2023)
Objective: The present study’s is to develop floating drug delivery system of repaglinide. Methods: Moringa gum, Repaglinide, HPMC K100M, Sodium alginate, Calcium Carbonate, Sodium Citrate. The obtained formulation was evaluated for drug content, pH, in vitro gelling capacity, in vitro buoyancy studies, and in vitro dissolution studies. Results and Discussion: All the total F1-F12 formulations showed pH ranging from 5.1 to 7.9, floating lag time of F1-F12 ranging from 5 s to 12 s with total floating time greater than 12 h, viscosity of F1-F12 ranging from 619 to 3856 cp, drug content of F1-F12 ranging from 31.2% to 93.1%, and percent drug release of F1-F12 ranging from 78.9% to 93.9%. Dissolution studies showed that F12 formulation-containing drug (30 mg) and polymer (4000 mg) showed 93.9% drug release in 12 h which is said to be optimized. Thus, the best formulation (F12) was subjected for a 3-month period of stability studies found to be stable and reported no significant change. Conclusion: The study’s goal is to develop and evaluate floating in situ gel forming solution of repaglinide with moringa gum as rate retardant polymer.